PEMBUATAN DAN KARAKTERISASI KOMPOSIT SERAT KULIT JAGUNG DENGAN MATRIKS EPOKSI - eldo jones surbakti (Saintia Fisika, 2013)
Preparation and characterization of corn husk fiber composites with epoxy matrix by the method of Chopped Strand Mat the fiber composition: 0%, 1%, 2%, 3%, 4%, 5% have done well. The physical properties and mechanical properties of composites were obtained as density of 1.07 g/cm3 - 1.25 g/cm3, water absorption 0.75% - 3.55%, water content 0.90% - 4.33%, tensile strength 7.73 MPa - 10.02 MPa, 28.62 MPa flexural strength - 55.62 MPa, 3 kJ/m2 strong impact - 18.6 kJ/m2. The results showed physical properties and mechanical properties are almost the same as the Standard JIS A 5905:2003. It means the material used on this reseand can be applied to outomotive car such as bumper.Key words : epoxy, composites, corn huskfibers, physical properties, mechanical properties.